Polityka państwa dotycząca dostępu osób cywilnych do broni w kontekście wojny na Ukrainie i pandemii Covid-19 - Nowakowski, Bartosz (PRAWO i WIĘŹ, 2024)
The aim of this article is to present the impact of state policy on civilians’ access to weapons in the context of the war in Ukraine and Covid-19 pandemic. In the context of the above mentioned research objective, the article examines all currently possible forms of civilian access to weapons in the Republic of Poland: sport, hunting, collecting, personal protection, protection of persons and property, historical reconstructions, commemoration, training and others. In the first part of the discussion, the statistical data of the Police Headquarters on the access of civilians to weapons were analyzed. Then, the shortcomings of the current law were pointed out and de lege ferenda proposals for the most urgent and necessary legislative changes were made. The need for urgent legislative and administrative changes in the area of the current law was pointed out, with special emphasis on its adaptation to EU directives. It was recommended that there was an urgent need to introduce an electronic system for the collection and analysis of data on weapons permits, as required by the EU Directive; the need to adapt the categories of weapons contained in the EU Directive to the UoBiA; to move away from "to-target" permits to four levels of permits and to move away from specifying the number and type of weapons in the administrative decision; and finally, to regulate at the legislative level the rules for the storage of weapons, which are currently regulated by an implementing regulation.